Repair of a Late Presentation Thoracic Aortic Aneurysm following Coarctation Repair - Moon, Robert J.; Spadaccio, Cristiano; Duncan, Andrew J.; Bittar, Mohamad N. (AORTA, 2023)
We report the case of a 44-year-old gentleman who underwent coarctation repair at the age of 7 years. He was lost to follow-up and represented. Computed tomography scan demonstrated a 9.8-cm diameter aortic aneurysm involving the distal aortic arch and proximal descending aorta. Open surgery was performed to repair the aneurysm. The patient made an unremarkable recovery. He was followed up 12 weeks later, and significant improvement in preoperative symptoms was observed. This case demonstrates the importance of long-term follow-up.
Keywords: aortic; aneurysm; coarctation; repair